Object oriented programming: A practical guide using java - Kasmuri, Emaliana (Penerbit UTem Press, 2022)
Object-Oriented Programming: A Practical Guide Using Java provides a comprehensive introduction to object-oriented programming (OOP) principles using Java. It covers fundamental concepts such as encapsulation, inheritance, polymorphism, and abstraction, along with their practical applications in software development. With a hands-on approach, this book includes code examples, case studies, and exercises to help readers grasp and master OOP effectively. Ideal for students, educators, and programmers looking to enhance their Java skills for modern application development.